Pengaruh Lingkungan Kerja, Kompensasi dan Pengembangan Karir Terhadap Turnover Intention Karyawan (Studi Kasus PT Enkei Indonesia) - Alifah Putri Hidayah; Iin Inayah; Efi Riyana; Virgiawan Khasogi; Safitri Ashiama (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This research aims to determine the influence of the work environment, compensation and career development on turnover intention.This research was conducted on PT Enkei Indonesia employees aged 20-30 years on a vocational/equivalent education scale, D3 and S1. By using the lemeshow formula, 60 respondents were obtained. Hypothesis testing used Validity Test, Rehabilitation Test, Classical Assumption Test, Multiple Linear Regression, and F Test and T Test.The analysis carried out was Multiple Regression analysis and T Test. Based on the results of testing and discussion, the environment partially has a negative and insignificant effect on turnover intention of PT Enkei Indonesia employees with results of 0.512 > 0.05 and T count of 0.661. Partially, the level of employee compensation at PT Enkei Indonesia has a positive and significant effect of 0.008<0.05 and T count of 2,748. Partially, the level of career development at PT Enkei Indonesia has a negative and insignificant effect with results of 0.156> 0.05 and T count of 1.432. The coefficient of determination (R2) is 0.182, meaning that the percentage contribution to the influence of the work environment, compensation and career development of PT Enkei Indonesia employees is 18.2% and the remaining 81.8% comes from other variables not studied.